Genetic Determinants of Unruptured Intracranial Aneurysms in the General Population. Issue 10 (October 2015) - Peymani, Abbas; Adams, Hieab H.H.; Cremers, Lotte G.M.; Krestin, Gabriel; Hofman, Albert; van Duijn, Cornelia M.; Uitterlinden, André G.; van der Lugt, Aad; Vernooij, Meike W.; Ikram, M. Arfan
<x xml:space="preserve">Abstract</x> Background and Purpose— Genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) for intracranial aneurysms in clinical samples. In addition, SNPs have been discovered for blood pressure, one of the strongest risk factors for intracranial aneurysms. We studied the role of these genetic variants on occurrence and size of unruptured intracranial aneurysms, discovered incidentally in a general community-dwelling population. Methods— In 4890 asymptomatic participants from the Rotterdam Study, 120 intracranial aneurysms were identified on brain imaging and segmented for maximum diameter and volume. Genetic risk scores (GRS) were calculated for intracranial aneurysms (10 SNPs), systolic blood pressure (33 SNPs), and diastolic blood pressure (41 SNPs). Results— The GRS for intracranial aneurysms was not statistically significantly associated with presence of aneurysms in this population (OR, 1.16; 95% CI, 0.96–1.40; P=0.119), but showed a significant association with both maximum diameter (difference in log-transformed mm per SD increase of GRS, 0.10; 95% CI, 0.02–0.19; P=0.018) and volume (difference in log-transformed µL per SD increase of GRS, 0.21; 95% CI, 0.01–0.41; P=0.040) of aneurysms. GRSs for blood pressures were associated with neither presence nor size of aneurysms. Conclusions— Genetic variants previously identified for intracranial aneurysms in clinical studies relate to the size rather than the presence of incidentally discovered, unruptured intracranial aneurysms in the general population.